Penurunan Intensitas Nyeri Persalinan Kala 1 Fase Aktif dengan Terapi Murottal Al-Qur’an - Sri Mulyani Nurhayati; Siti Ulfah Nurjanah (Journal of Telenursing (JOTING), 2020)
The purpose of this study was to study how to analyze the intervention of giving marital therapy to decrease the intensity of labor in the first stage of the active phase in the Walnut Room of Pelni Hospital in Jakarta. The type of descriptive research chosen for the investigation to be carried out is a case study. The results of the survey before the administration of marital therapy found that subject I had a chance, pain scale 7 (severe pain), looked anxious, tense, pain disappeared, facial expressions grimaced. While in subject II who initially experienced a pain scale of 6 (moderate pain), looked worried, facial expressions appeared to wince. After the intervention of marital therapy, it was found that subject I had a chance, pain scale 6 (moderate pain). Conclusion, treatment of Murottal AlQuran therapy affects decreasing pain intensity. Keywords: Murottal Al-Qur'an, Pain, Childbirth